2019
DOI: 10.1016/j.bone.2019.07.023
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of mortality after postoperative infection in hip fracture patients

Abstract: Background: Postoperative infection is a common complication in hip fracture patients and the risk appears to have increased during the last decade. However, the impact of infection on mortality after hip fracture surgery remains unclear. Purpose: We aimed to examine the association between infection (any, as well as specific infections), with all-cause mortality following hip fracture surgery. Methods: Using Danish nationwide registries, we conducted a population-based cohort study on 74,771 hip fracture pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 31 publications
(44 reference statements)
0
29
0
Order By: Relevance
“…[6][7][8] It not only leads to more hospital stay, poor functional outcomes, and greater costs but also results in a substantially increased mortality risk. 9,10 A variety of risk factors of SSI were documented, including age, comorbidities, obesity, the experience of the surgeon, haematoma, surgical duration, increased duration of anaesthesia, body mass index (BMI), current smoking, preoperative hospital stay, serum albumin, warfarin treatment, and so forth. 6,11,12 As reported by Harrison, 13 the method of fracture fixation was also significantly associated with the SSI.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] It not only leads to more hospital stay, poor functional outcomes, and greater costs but also results in a substantially increased mortality risk. 9,10 A variety of risk factors of SSI were documented, including age, comorbidities, obesity, the experience of the surgeon, haematoma, surgical duration, increased duration of anaesthesia, body mass index (BMI), current smoking, preoperative hospital stay, serum albumin, warfarin treatment, and so forth. 6,11,12 As reported by Harrison, 13 the method of fracture fixation was also significantly associated with the SSI.…”
Section: Introductionmentioning
confidence: 99%
“…13 Several studies identify postoperative pneumonia as a predictor of short-term and long-term mortality after surgery. [14][15][16][17][18][19] Is there a difference in the outcomes of postoperative pneumonia between patients with and without T2DM?…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31] In addition, associations between transfusion practice and outcome, 32,33 association between surgery delay and post-operative complications, 34,35 associations between some commonly used medication preoperatively, including antidepressants, anticoagulants and anti-inflammatory drugs and post-operative complications [36][37][38][39][40] have been observed. Moreover, studies have found that about 15% of hip fracture patients develop an acute kidney injury within 5 days of surgery 41,42 and about 15% of patients sustain postoperative infections within 30 days of surgery, 43,44 complications which are strongly associated with 30 days mortality. Besides, hip fracture patients were at increased excess risk of venous thromboembolism, myocardial infarction and stroke up to one year following fracture.…”
Section: Examples Of Researchmentioning
confidence: 99%